Kritik Implementasi Corporate Social Responsibility Terhadap Indeks Kepuasan Masyarakat - Aji Dedi Mulawarman; Siti Dian Nur'aini (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This research aims to determine how much influence the implementation of the CSR programs has on the Community Satisfaction Index obtained by PT Semen Indonesia (Persero) Tbk Tuban business unit in the sustainability report. Uses a descriptive approach with the method of Critical Discourse Analysis. Data were obtained through interviews and company IKM/sustainability reports. Based on the results of data analysis, the value of the CSR IKM of PT Semen Indonesia (Persero) Tbk's Tuban business unit was 79.05% in the 2020 and 2021 sustainability reports, indicating that the CSR program is included in the